Progress report for the first twenty-one months of the contract period (Franklin Pierce Law Center, Concord, NH (USA). Energy Law Inst., 1980)
During the period of July 1, 1978, through March 31, 1980 in-depth research of the legal and institutional obstacles and incentives to the development of small scale hydroelectric power in all of the nineteen northeastern states was performed. Research into economic issues associated with the development of small scale hydroelectric power was undertaken by the project economist. Special research activities have been undertaken with respect to the federal dam safety programs, the National Pollution Discharge Elimination System requirements of the Federal Clean Water Act and the implications of those requirements to small scale hydroelectric power, riparian law on lake and reservoir fluctuation in the State of Maine, and the implications of Title II and IV of the Public Utility Regulatory Policies Act of 1978 to the development of small scale hydroelectric power. The results of these studies are reported. (LCL)